The Effects of External Jugular Compression Applied during Head Impact Exposure on Longitudinal Changes in Brain Neuroanatomical and Neurophysiological Biomarkers: A Preliminary Investigation - Myer, Gregory D.; Yuan, Weihong; Barber Foss, Kim D.; Smith, David; Altaye, Mekibib; Reches, Amit; Leach, James; Kiefer, Adam W.; Khoury, Jane C.; Weiss, Michal; Thomas, Staci; Dicesare, Chris; et al. (Frontiers in Neurology, 2016)
*